Relaparotomy Two Years after Incisional Hernia Repair Using a Free Fascia Lata Graft - Yuuki Sekine; Hiroyuki Sugo; Naoki Iwanaga; Shigefumi Neshime; Ikuo Watanobe (Case Reports in Surgery)
Although, free fascia lata autografts can be used to reconstruct various anatomical structures, little information is available about the status of such autografts several years after the procedure, especially in a clinical setting. Here, we describe our experience with a patient who underwent relaparotomy two years after incisional hernia repair using a fascia lata graft. A 79-year-old man underwent open hepatectomy for hepatocellular carcinoma. One year later, abdominal computed tomography revealed a locally recurrent tumor 1.5 cm in diameter and a giant incisional hernia measuring approximately 15×6 cm on the supraumbilical midline. After repeat hepatectomy, the incisional hernia was repaired using a free fascia lata patch as an interpositional graft. Two years later, the patient was readmitted because of recurrent tumors in the liver, and repeat hepatectomy was performed. During surgery, the fascia lata graft had survived well and become incorporated into the native fascia. We incised this fascia lata graft in the same way as for a normal laparotomy. After hepatectomy, the fascia lata graft was closed in layers with interrupted sutures. The patient was discharged on postoperative day 11 with no wound-related morbidity.